1991
DOI: 10.1128/mcb.11.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Deletion or substitution within the alpha platelet-derived growth factor receptor kinase insert domain: effects on functional coupling with intracellular signaling pathways.

Abstract: The tyrosine kinase domains of the platelet-derived growth factor (PDGF) and colony-stimulating factor-i (CSF-1)/c-fins receptors are interrupted by kinase inserts (ki) which vary in length and amino acid sequence.To define the role of the ki in the human aPDGF receptor (aPDGFR), we generated deletion mutants, designated aRAki-1 and aRAki-2, which lacked 80 (710 to 789) and 95 (695 to 789) amino acids of the 104-amino-acid ki region, respectively. Their functional characteristics were compared with those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…The PDGF-AB isoform has been reported to possess the strongest ability to induce a mitogenic response in cells expressing both a-and b-receptors (Heidaran et al, 1991;Rupp et al, 1994). We have therefore investigated the possible unique features of the heterodimeric PDGF receptor complex compared to the homodimeric complexes, and found that in the heterodimeric complex activation of Ras and Erk2 MAP kinase were stronger and more sustained compared to homodimeric complexes (Ekman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The PDGF-AB isoform has been reported to possess the strongest ability to induce a mitogenic response in cells expressing both a-and b-receptors (Heidaran et al, 1991;Rupp et al, 1994). We have therefore investigated the possible unique features of the heterodimeric PDGF receptor complex compared to the homodimeric complexes, and found that in the heterodimeric complex activation of Ras and Erk2 MAP kinase were stronger and more sustained compared to homodimeric complexes (Ekman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include heteromeric complexes of members of the epidermal growth factor receptor family Solto et al, 1994;Wada et al, 1989;Heidaran et al, 1991;Kanakaraj et al, 1991;Seifert et al, 1989). PDGF is a family of dimeric isoforms of related A-and Bpolypeptide chains, which exert their cellular eects by binding to two structurally similar tyrosine kinase receptors.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the e ects of the deletion mutant on the ligand-dependent and independent tyrosine phosphorylation of a and bPDGFRs endogenously expressed in NIH3T3 cells (Heidaran et al, 1991;Seifert et al, 1989), total cell lysates prepared from untreated or PDGF-BB treated NIH3T3 or NIH3T3/ aR D235 ± 290 cells were subjected to immunoblot analysis using anti-P-Tyr. Consistent with the size of the deletion mutant, a protein species with molecular weight of about 180 kDa was speciÂźcally phosphorylated on tyrosine in NIH3T3/aR D235 ± 290 (Figure 4a, lane 3).…”
Section: Resultsmentioning
confidence: 99%
“…The PDGF system is complicated in that three PDGF isoforms comprised of homo or heterodimers of A and B chains di erentially interact with a and b PDGF receptors (PDGFRs) encoded by two distinct genes (Claesson-Welsh et al, 1988;Matsui et al, 1989a;Yarden et al, 1986). Moreover, there is accumulating evidence that PDGF activation involves recruitment of receptor dimers (Bishayee et al, 1989;Heidaran et al, 1991;Heldin et al, 1989;Seifert et al, 1989;Ueno et al, 1991). In Âźbroblasts where both PDGFRs are expressed, PDGF-BB activates ab, bb and aa receptor dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation